Pemberdayaan Masyarakat Melalui Pengelolaan Sampah Plastik di Dusun Ngagel, Kabupaten Madiun - Fajarwati, Riska Indah; Yunita, Ratna (LPkM Universitas Bakrie, 2022)
Plastic waste is the main source of problems in contributing to the accumulation of waste weight, especially plastic that takes a very long time to decompose. The 3R principles include Reduce, Reuse, and Recycle are ways that can be applied in dealing with plastic waste. The purpose and activity of this community service is to foster public interest in utilizing plastic waste into useful goods. In addition, it is also to mobilize the surrounding community to be aware of maintaining environmental cleanliness and health through good and correct waste management. In this case, waste management is carried out by utilizing plastic waste, such as used bottles and used oil containers as plant pots. The community service method used is the Asset Based Community Development approach, namely by using assets owned and Ngagel in the form of plastic waste and then recycling them into plant pots. The implementation of the service activities as a whole has gone well and can be said to be successful. The result of this community service is a decrease in the amount of unprocessed plastic waste which has implications for the increasing awareness of the Ngagel hamlet community in waste management and can make plastic waste as an alternative to environmentally friendly plant pots.